FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS TIDUR PADA PASIEN CONGESTIVE HEART FAILURE - ', Fachrunnisa '; Nurchayati, Sofiana '; ', Arneliwati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Congestive Heart Failure (CHF) is a cardiovascular disease which shows a variety symptoms (dyspnea, edema, chest pain, anxiety, fatigue) that affect the sleep quality of patient. The purpose of the research is identify the factors that associated with quality of sleep in patients with CHF especially chest pain, anxiety, Paroxysmal Nocturnal Dyspnea (PND), and fluids overload. The design was descriptive correlational research with cross sectional study. Samples of this research was taken by using purposive sampling technique, which 32 patients with CHF in Flamboyan ward Arifin Achmad General Hospital Pekanbaru. This research used questionnaire Pittsburgh Sleep Quality Index (PSQI) for quality of sleep, Numeric Rating Scale (NRS), and Hamilton Anxiety Rating Scale (HARS). The univariate analysis showed that majority patient of CHF was 45-60 years old (43,8%), women (53,1%), unemployment (59,4%), once history of hospitalization (31,3%), medium pain (37,5%), no anxiety (40,6%), PND (56,3%), no edema (81,3%) and poor quality of sleep (62,5%). The bivariate analysis was conducted by using chi-square and kolmogorov-smirnov test showed there are a correlation between anxiety Ï value (0,001)< Î± (0,05) and breathing Ï value (0,008)< Î± (0,05) with quality of sleep in patients CHF and there are no correlation between pain Ï value (0,925)> Î± (0,05) and fluid overload Ï value (0,985)< Î± (0,05) with quality of sleep in patient CHF. Recommended for nurse to give a nursing care to decrease anxiety and PND by create a pleasant environment, suitable position, oxygenation and an ideal bed to improve quality of sleep in patient with CHF. KeywordsÂ Â Â Â Â Â Â Â Â Â Â Â Â : Anxiety, chest pain,congestive heart failure, edema, quality of sleep References Â Â Â Â Â Â Â Â Â Â : 81 (2000-2015)